Life with an Indwelling Urinary Catheter: Experiences from Male Patients Attending the Urology Clinic at a Tertiary Hospital in Northwestern Tanzania-A Qualitative Study - Asteria L. M. Ndomba; Rose M. Laisser; Eveline T. Konje; Joseph R. Mwanga; Stephen E. Mshana (MDPI AG, 2022)
Experiences from patients living with a long-term indwelling urinary catheter (IUC) at home among men attending urology clinics have not been reported. Evidence-based information on such experiences is important for improving nursing care in low- and middle-income countries such as Tanzania. Using a descriptive phenomenological qualitative research design, we observed two main themes: "Adjustments to positive living with a catheter at home", denoting that social interaction and psychological and spiritual support are important to positively live with the catheter, and "The home environment influences negative or positive living", considering intimacy and altered body image to significantly influence the ability to practice sex, leading to wives' self-sacrifice. Respondents experienced difficulties in living with a long-term IUC at home due to a lack of information from healthcare professionals on how to manage their catheters and urine bags. In adjusting to positive or negative living with a catheter at home, respondents had to figure out strategies to minimize psychological and emotional trauma and hasten the adjustment process. A clear guideline or checklist is needed to ensure that all important information is provided by health professionals at the time of discharge and during subsequent visits to patients on how to care for the catheter insertion sites and help them adjust to living with a long-term IUC.